2020
DOI: 10.20321/nilejbe.v6i16.01
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Real Exchange Rate Changes on External Trade Balance in Sudan: Testing J-Curve Hypothesis

Abstract: The current research article analyzes the impact of changes in real exchange rate upon external trade balance of Sudan during the period 1978-2017. It employs Autoregressive Distributed Lag (ARDL) approach, impulse response functions and Granger causality test. The empirical findings indicate that exchange rate devaluations have no impact on the merchandize trade balance, thus evidence in favor of the J-curve pattern was not found. Granger causality test runs one-way from trade ratio to real exchange rate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…As shown in Table (7), we cannot reject the hypothesis that neither variable Granger-causes the other. These results are in line with Ibrahim & Bashir, [36].…”
Section: Tests For Serial Correlation and Granger Causalitysupporting
confidence: 92%
See 4 more Smart Citations
“…As shown in Table (7), we cannot reject the hypothesis that neither variable Granger-causes the other. These results are in line with Ibrahim & Bashir, [36].…”
Section: Tests For Serial Correlation and Granger Causalitysupporting
confidence: 92%
“…Both tables show that in all cases, the unit root hypothesis cannot be rejected. Therefore, It can be concluded that most variables are I (1), except for trade balance, which was stationary at level, a result confirmed by numerous other studies such as Ibrahim and Bashir [36]; Bashir and Ibrahim, [50]; Ibrahim and Bashir, [53]; Wu [54].…”
Section: Unit Root Testssupporting
confidence: 75%
See 3 more Smart Citations